Deciphering Familiar Conundrum of Cerebral Salt Wasting Syndrome vs Syndrome of Inappropriate Secretion of Antidiuretic Hormone and Establishing Role of Hyponatremia in Patients of Tuberculous Meningitis as a Predictor of Outcome. - Kulwant Singh; Yadav, Vikrant (Nepal Journal of Neuroscience, 2024)
Introduction: Hyponatremia is one of the most common electrolyte abnormalities [35-71%] associated with tuberculous meningitis [TBM]. It is an independent predictor of patient outcome. Cerebral salt wasting syndrome [CSWS] and syndrome of inappropriate secretion of antidiuretic hormones [SIADH] are two common causes of hyponatremia in patients with TBM. This study targets patients with tuberculous meningitis to provide a detailed analysis of hyponatremia in TBM patients and it’s predictive value in terms of outcome and also describes the distinguishing features of CSWS and SIADH. Materials and methods: This was a clinical, prospective study of 31 patients with TBM in which various parameters were analysed . Serial sodium levels were recorded on the day of admission, day 2, 7 and 28. Patients with hyponatremia were divided into CSWS and SIADH. Results: In this study, 24[77.42%] patients had hyponatremia. In 14 [58%], hyponatremia was due to CSWS and in 10[42%] of the patients with hyponatremia it was SIADH. Hyponatremia was related to disease severity, GCS score, hospital stay, ventilator stay and patient outcome. CSWS was more strongly associated with disease severity than SIADH. Conclusion: Hyponatremia is a common electrolyte imbalance in patients with TBM and a direct and valid predictor of disease outcome. CSWS should be differentiated from SIADH due to the different treatment strategies.